2020
DOI: 10.1088/2053-1591/ab61b1
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen annealing effect on resistive switching characteristics of multilayer CeO2/Al/CeO2 resistive random-access memory

Abstract: Cerium oxide-based memristors have been extensively studied because of their compatibility with CMOS technology. Yet, inconsistency of resistive switching parameters is one of the main contests in development of nonvolatile memory for commercialization. Owing to filamentary nature of the resistive switching devices, variability of the resistive switching characteristics can be reduced by doping, where conductive filaments can easily grow due to reduction in the formation energy of oxygen vacancies. In this wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Hence, an alternative conduction mechanism with nonexponential voltage dependence is required. Such a characteristic is found in the space-charge limited current (SCLC) model, which is frequently used to explain the transport in VCM cells. ,,− …”
Section: Analysis Of the Conduction Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, an alternative conduction mechanism with nonexponential voltage dependence is required. Such a characteristic is found in the space-charge limited current (SCLC) model, which is frequently used to explain the transport in VCM cells. ,,− …”
Section: Analysis Of the Conduction Mechanismmentioning
confidence: 99%
“…To verify this type of conduction, the I–V dependence is measured and plotted on a double logarithmic scale, which allows determination of the power law I ∝ V α by a linear regression. ,,− An example from the work of Maikap of this approach is shown in Figure for a W/TaO x /TiN cell. The slopes α determined in resistive switching devices differ strongly, and the values in the referenced literature are found between 0.8 and 21. , …”
Section: Analysis Of the Conduction Mechanismmentioning
confidence: 99%
“…In this case, the formation of CFs will not be dispersed throughout the doped composite for RS material used between electrodes in RRAM devices. This will reduce the variability 11 and improve the RS behavior of ATiO 3. 55 Previous studies reported the role of formation and rupturing of CFs in controlling the RS behavior 56,57 .…”
Section: Charge Densitymentioning
confidence: 99%
“…A significant increasing factor of RRAM is its simple structure of RRAM exhibiting better RS behavior because of long retention, low power consumption, small size, and high‐density integration 6‐10 . Inherently low voltage (<2 V) 11 and power consumption of RRAM leverage them in the industry of energy saving devices 2,12‐14 . The review of Chakraborty et al was focused on low energy aspect of NVM and their application in energy efficient memory and computing devices 15 .…”
Section: Introductionmentioning
confidence: 99%
“…6 . Such types of variations have been noticed in many RRAM devices such as Pt/Ti/CeO 2 /Al/CeO 2 /Pt 48 and particularly in devices with TaN as top electrode like TaN/CeO 2 /Al/CeO 2 /Pt 49 and TaN/CeO 2 /Ti/CeO 2 /Pt 50 devices. Such behavior causes variations in HRS/LRS ratio from device to device.…”
Section: Resultsmentioning
confidence: 83%